Increase the threshold voltage of high voltage GaN transistors by low temperature atomic hydrogen treatment; Semiconductors; Vol. 51, iss. 2 - Erofeev E. V. Evgeny Viktorovich; Fedin I. V. Ivan Vladimirovich; Kutkov I. V. Iljya Viktorovich; Yuriev Yu. N. Yuri Nikolaevich (Physics of Semiconductor Devices, 2017)
Title screen